ANALISIS HUBUNGAN INFLASI DAN PERTUMBUHAN EKONOMI DI INDONESIA 1970 (I) â 1995 (IV) Analysis of the Relationship between Inflation and Economic Growth in Indonesia 1970 (I) - 1995 (IV) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT This study examines the relationship between inflation rate and economic growth in Indonesia. The variables involved in this study are real Gross Domestic Product as dependent variable, and uncertainty prices, real wages, values of real import on raw materials and on intermediate goods, real credits and productivity as independent variable. The method used to estimate the parameters is Ordinary Least Square (OLS) through Double Log Linear Model. Data used is this study in secondary data, a quarterly data, mostly acquired from International Financial Statistics (IFS), Statistic of Indonesia and Economy Indicator from Central Beareau of Statistics (BPS) as well as other sources which related to this study, ranging from 1970 (I) to 1995 (IV). Results of this study are as follows : 1. Using t-statistics with 5% significant level, each of the independent variables (5 variables) significantly explains the dependent variable. The R-Square is 0,93, which means that the independent variables all together explains 93% of the variance of the dependent variable. Futhermore, the overall analysis shows that all of the independent variables significantly explains the change of the dependent variable. 2. For short term, the relationship between inflation rate and economic growth is positive. Every 10% increase in uncertainty price will increase the Gross Domestic Product by 1,41% (ceteris paribus). The increase of uncertainty prices is inflation phenomena and shows the trade-off between inflation rate and unemployment in Indonesia. Whereas in the long-run, every 10% increase of uncertainty prices will decrease the Gross Domestic Product by 4%. Thus in the long-run, inflation rate moves in the same direction as the unemployment rate. Since each economic policies designed by the government should be long-run oriented, i.e. effort to